Brucella Species Infection of Ventricular-peritoneal Shunt: A Rare form of Neurobrucellosis Presenting as an Intra-abdominal Mass - Nawal A Al-Kindi; Aisha A Al-Bulushi; Qasim S Al-Hinai; Nuha A Al Tahir; Khalsa Al-Ramadhani; Amal S Al-Maani (International Journal of Innovative Research in Medical Science, 2021)
A 12-year-old girl with right cerebellar pilocytic astrocytoma and left Ventricular – Peritoneal (VP) shunt presented with prolonged progressive painful abdominal distention, constipation, significant weight loss and intermittent fever. Laboratory investigations including blood and CerebroSpinal Fluid (CSF) tests revealed a VP shunt infection with Brucella abortus + Brucella melitensis. Abdominal Computed Tomography (CT) scans revealed a large abdominopelvic cyst with enhancing wall suspicious for infected pseudocyst. Ovarian tumor markers including AFP, CA-125, CA 19-9 and CEA were negative. Brucella was detected in cyst fluid by Real Time -Polymerase Chain Reaction (RT -PCR). The patient had her infected shunt removed, with establishment of External Ventricular Drainage (EVD) and treatment with antibiotics. A final diagnosis of neurobrucellosis was made and she responded well to 6 months therapy of oral doxycycline, oral rifampicin and oral cotrimoxazole. This case highlights a rare occurrence of neurobrucella in patients with VP shunts and excellent response to source control and antimicrobial therapy.